RA02.03: THERAPEUTIC STRATEGY FOR ADENOCARCINOMA OF ESOPHAGO-GASTRIC JUNCTION. (14th September 2018) - Yago, Akikazu; Akiyama, Hirotoshi; Sato, Kei; Sato, Sho; Tanaka, Yusaku; Miyamoto, Hiroshi; Kosaka, Takashi; Kunisaki, Chikara; Endo, Itaru
Abstract: Background: The optimal surgical management for adenocarcinoma of the esophagogastric junction, including surgical approach, range of nodal dissection, and type of gastrectomy remains controversial. Methods: In our two institutions, from January 2001 to September 2016, we retrospectively analyzed clinicopathological factors and long-term results of 72 patients who underwent radical resection and evaluated the priority of nodal dissection based on the therapeutic value index [ = the frequency of lymph node metastasis (%) x the 5-year survival rate (%)/100] and recurrence pattern. Results: Median age:66 (44–94), male/female = 54/18, TG/PG = 60/12, Tumor size < 40mm/ ≥ 40mm = 32/40, pT1/2/3/4 = 14/13/28/17, pN0/1/2/3 = 32/17/8/15, intestinal/diffuse type = 39/33. pStageI/II/III = 29/17/26, 5-year survival rates were pStageI/II/III = 91.1/86.2/51.4%. Univariate analysis revealed that tumor size ≥ 40mm (vs < 40mm, P  = 0.009), diffuse type (vs intestinal type, P  = 0.0031) and pN2–3 (vs pN0–1, P  < 0.001) patients had significantly poor prognosis, and multivariate analysis revealed that diffuse type ( P  = 0.018, HR 3.991, 95%CI 1.264–12.606) and pN2–3 ( P  = 0.040, HR 3.112, 95%CI 1.055–9.183) were independent prognostic factors. The therapeutic value index of nodal dissection was No.1/2/3/7/11d/parahiatal/lower mediastinal = 15.56/12.34/11.34/7.05/5.40/12.04/2.70, and no evidence of lymphadenectomy was observed for No.4, 5, 6, 10, 16, upper and middle mediastinum. 19 cases had disease recurrence, 3 cases were mediastinal lymph node recurrence. Conclusion: Our study showed that distal gastric lymph nodes dissection is unnecessary, and gastrectomy with lower mediastinal and proximal gastric lymph node dissection is recommended for the treatment of adenocarcinoma of EGJ. Since diffuse type and pN2–3 were independent prognostic factors even after potentially curative resection, so additional chemotherapy might be required for such cases. Disclosure: All authors have declared no conflicts of interest.